Bihemispheric-tDCS and Upper Limb Rehabilitation Improves Retention of Motor Function in Chronic Stroke: A Pilot Study - Goodwill, Alicia M.; Teo, Wei-Peng; Morgan, Prue; Daly, Robin M.; Kidgell, Dawson J. (Frontiers in Human Neuroscience, 2016)
Background: Single sessions of dual transcranial direct-current stimulation (dual-tDCS) with concurrent rehabilitation improves motor function in stroke survivors, which outlasts the stimulation period. However few studies have investigated the behavioural and neurophysiological adaptations following a multi-session intervention of dual-tDCS concurrent with rehabilitation. Objective: This pilot study explored the immediate and lasting effects of 3-weeks of dual-tDCS and upper limb (UL) rehabilitation on motor function and corticospinal plasticity in chronic stroke survivors. Methods: Fifteen chronic stroke survivors underwent 3-weeks of UL rehabilitation with sham or real dual-tDCS. UL motor function was assessed via the Motor Assessment Sale (MAS), Tardieu Scale and grip strength. Corticospinal plasticity was indexed by motor evoked potentials (MEPs), cortical silent period (CSP) and short-interval intracortical inhibition (SICI) recorded from the paretic and non-paretic ULs, using transcranial magnetic stimulation (TMS). Measures were taken at baseline, 48 hours post and 3-weeks following (follow-up) the intervention. Results: MAS improved following both real-tDCS (62%) and sham-tDCS (43%, P < 0.001), however at 3-weeks follow-up, the real-tDCS condition retained these newly regained motor skills to a greater degree than sham-tDCS (real-tDCS 64%, sham-tDCS 21%, P = 0.002). MEP amplitudes from the paretic UL increased for real-tDCS (46%: P < 0.001) and were maintained at 3-weeks follow-up (38%: P = 0.03), whereas no changes were observed with sham-tDCS. No changes in MEPs from the non-paretic nor SICI from the paretic UL were observed for either group. SICI from the non-paretic UL was greater at follow-up, for real-tDCS (27%: P = 0.04). CSP from the non-paretic UL increased by 33% following the intervention for real-tDCS compared with sham-tDCS (P = 0.04), which was maintained at 3-weeks follow-up (24%: P = 0.04). Conclusions: Dual-tDCS improved retention of gains in motor function, which appears to be modulated through intracortical inhibitory pathways in the contralesional primary motor cortex (M1). The findings provide preliminary evidence for the benefits of dual-tDCS during rehabilitation. Larger clinical trials are warranted to examine long term benefits of dual-tDCS in a stroke affected population.